New species and new records of eunicids (Polychaeta, Eunicidae) from Taiwan - Hsueh, Pan-Wen; Li, Yan-Huei (Zootaxa, 2014)
Seven species of eunicids were found from rocky intertidal and shallow subtidal habitats on the coasts of Taiwan. These polychaetous worms belong to two genera, Eunice Cuvier, 1817 and Nicidion Kinberg, 1865. Among them, five species are new to science, namely Eunice jihueiensis sp. nov., Eunice reticulata sp. nov., Eunice shihmenensis sp. nov., Eunice taoi sp. nov., and Nicidion megabalanicola sp. nov., Eunice annulicirrata Miura, 1986 and Eunice dilatata Grube, 1877, are documented for the first time from this geographic region. A key to the genus and species of these eunicids is provided.